Effects of semi-deep water irrigation on hybrid indica rice lodging resistance - Gao, Hui; Dou, Zhi; Chen, Linrong; Lu, Yao; Sun, Dong; Xu, Qiang; Sun, Ruyin; Chen, Xueying (Frontiers in Plant Science, 2022)
Recently, rice-aquatic animal integrated farming (RAAIF) has grown rapidly in China due to its favorable benefits and the lower application of pesticides and fertilizers. However, rice lodging occurs frequently under RAAIF, which restricts rice yield. We assumed that semi-deep water irrigation may cause weaker rice-lodging resistance since it is the most significant environmental factor for RAAIF that distinguishes it from rice monoculture. To investigate the response of rice stem lodging resistance to semi-deep water irrigation and its mechanism, three irrigation management modes, namely the typical high-yield irrigation model that is mainly based on swallow and wetting (CK), semi-deep water irrigation from the late tillering stage to the jointing stage (SDI1), and semi-deep water irrigation from the jointing stage to the middle grain-filling stage (SDI2), were conducted using three hybrid indica rice varieties: Shenliangyou136 (SLY136), Huiliangyousimiao (HLYSM), and Wanxiangyou982 (WXY982). Mechanics analysis indicated that the bending moment by the whole plant (WP) and the breaking strength (M) were both decreased by semi-deep water irrigation when compared with CK, while M presented a larger decreasing amplitude than WP, which induced the increased lodging index (LI) of rice, for all the tested varieties. SLY136 and HLYSM were affected more strongly by SDI1, whereas WXY982 was affected more strongly by SDI2. Significant weaker breaking force under two semi-deep water irrigation modes contributed to the decreased M relative to CK. Morphology results showed that semi-deep water irrigation reduced the thickness of mechanical tissues, sclerenchyma cells, and parenchyma cells; reduced the number of vascular bundles; and caused a looser arrangement, inducing the lower fullness of the rice basal internode. Decreased accumulation of lignin and cellulose was also linked to the weaker breaking force of the basal internode under semi-deep water irrigation, which was verified by correlation analysis. WXY982 had obvious lower structural carbohydrates content under semi-deep water irrigation than the other two varieties and thus showed worse breaking force and LI. In conclusion, the worse mechanical strength of the rice basal internode under semi-deep water irrigation was closely associated with weaker vascular bundle development and suppressed structural carbohydrate accumulation, and the decreasing degree of lodging resistance varied between rice varieties and semi-deep water irrigation periods.